Consumer Trust in the Artificial Intelligence Era: Influence of Data Protection Practices on Purchase Intention - Ergün, Kutlu (Sustainable Governance in the Age of Artificial Intelligence: Interdisciplinary Perspectives on ESG, Digital Transformation and Corporate Responsibility, 2026)
This paper examines how data protection practices function as early indicators of trust and governance mechanisms in AI-driven, data-intensive digital markets. Within the digital economy, data-driven value creation through personalization, segmentation, and relationship management amplifies privacy and risk concerns, which subsequently influence the evolution of trust. Effective data protection and transparent communication are identified as critical determinants of market value. While structural cues are initially prominent, the website experience gains importance as user interactions progress. The expansion of data processing and sharing in AI environments further highlights the necessity of maintaining privacy balances. This article clarifies the essential role of open and standardized privacy communication in fostering consumer trust and enhancing market value, and discusses implications for marketing, policy, and future research. This study integrates previously fragmented discussions on privacy assurance, personal data control, transparency, perceived risk, and purchase intention into a concise conceptual framework. This framework explains how data protection practices function as trust-building mechanisms in AI-driven digital markets.